PENINGKATAN KOMPETENSI PROFESIONAL GURU MELALUI SUPERVISI AKADEMIK DENGAN TEKNIK T2SM - Hudaya (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2022)
This School Action Research aims to see the effectiveness of the academic supervision of the T2SM method in improving the professional competence of teachers at SMP Negeri 4 Depok in the 2020/2021 academic year. This research was conducted in odd semesters with 36 teachers as the object of research. Professional teachers are teachers who are able to carry out their duties in accordance with their responsibilities and professions according to their characteristics, among others; understand the task, collaborate effectively with students, parents of students, fellow teachers, and the community, able to develop themselves for the sake of improving services to students; able to direct, motivate and grow student behavior; and maintain the position code of ethics. The purpose of academic supervision is to help teachers develop skills, develop curricula, develop teacher working groups, and guide classroom action research to achieve the learning goals set for their students. The result of this research is that there is an increase in the number of teachers and the percentage of academic competence. It can be seen that 94.46% have completed learning administration, carried out classroom learning activities in accordance with the learning implementation plan, and have carried out an assessment in accordance with the assessment guidelines both on the assessment of attitudes, knowledge, and skills and have carried out item analysis. The use of the T2SM method has proven to be effective in improving the professional competence of teachers.